Pengembangan Program Bimbingan dan Konseling untuk Meningkatkan Perilaku Belajar Efektif di SMAN 4 Bandung - Cholil, Cholil (Jurnal Bimbingan dan Konseling Islam, 2019)
The aim of this research is to produce a guidance and counseling service program to improve effective learning behavior at SMAN 4 Bandung. This research is a research & development research. Participants in this study were guidance and counseling teachers at SMAN 4 Bandung, and 1 class X learning group 3. Natural data collection techniques used were Questionnaire, interview, observation and documentation. The questionnaire used in the setting of this study was a developmental task instrument (ITP), and a student problem needs instrument (IKMS), while the analysis technique used was data triangulation. The incoming data will be compared for cross-checking related to its validity. A guidance and counseling service program to improve effective learning behavior is divided into four stages. First is observation activities, second is assessment activities, third is program planning, fourth is program implementation activities, and the last is program evaluation. The result achieved was the formation of a guidance and counseling service program to improve effective learning behavior that was approved to be implemented at SMAN 4 Bandung. The validation related to the program by the expert (judgment expert) has been feasible to be implemented with several revisions according to the suggestion, overall it can be categorized well.